The construction and manipulation of temporal structures in Yeve cult music: A multi-dimensional approach - Avorgbedor, Daniel K. (International Library of African Music, 1987)
The purpose of this paper is, therefore, to investigate in detail how musical time is arrived at, and how it interacts with and is influenced by social events and by the specific context under which the music is performed. The analysis will be based upon examples from Yeve cult music as practised among the Anlo-Ewe of Ghana. In addition, the paper will examine relationships that exist between the individual or composite (musical and extra-musical) temporal structures and participants' affective response. The affective or experiential domain will also include audience response.
Keywords: African Music